An enzyme-free amplification strategy based on two-photon fluorescent carbon dots for monitoring miR-9 in live neurons and brain tissues of Alzheimer's disease mice. Issue 58 (16th June 2020) - Wu, Wenxiao; Zheng, Tingting; Tian, Yang
Abstract : An enzyme-free amplification strategy for monitoring alterations of miR-9 inside neurons of different stages of Alzheimer's disease mice. Abstract : An enzyme-free amplification strategy based on two-photon fluorescent carbon dots for monitoring miR-9 in live neurons and brain tissues of Alzheimer's disease (AD) mice. Notably, using our developed probe, miR-9 was found to be up-regulated in early onset AD, while it was found to be down regulated to lower than the normal level in late onset AD.